Beyond Disaster - Rosario, Melissa L. (Northwestern University Press, 2025)
An alternative view of Puerto Rico’s past, present, and futureHow do we map the pathways to liberation where we have been taught to see only trauma, suffering, and lack? Melissa L. Rosario offers an alternative view of Puerto Rico, America’s oldest colony, removing readers from the framework of crisis to consider the deeper legacies of its current impasse. Beyond Disaster: Building Collective Futures in Puerto Rico is an intimate portrait, weaving insights from the author’s own life, research, and organizing work as a scholar in the diaspora who rematriated. Rosario bridges the genres of social history and memoir to unsettle the meaning of resistance and freedom, underscoring the deep wounds of colonialism while still uplifting the profound possibilities of embodied alternatives.Beyond Disaster critiques the framework of debt and crisis by examining the psychological, emotional, and spiritual effects of colonialism. Rosario highlights key examples of organizing efforts to defend land and education against total enclosure, protecting life amid loss. This book offers a series of microhistories, vignettes, and prose poetry to foreground the daily practices necessary to anchor the ecological and political landscapes of our collective future.